Preparation method of zeolite in-situ loaded MnOOH composite catalyst and application thereof
Patent Information
- Application Number
- CN202410220930.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-02-28
AI Technical Summary
但是,越来越多的研究者发现沸石的酸性在碱性环境中不稳定,其Bronsted酸性位点在去质子化后易于与胺结合,无法进一步转移质子参与催化
[0019] 1. This invention uses only one hydrothermal method to grow MnOOH in situ on the surface of zeolite. The preparation process is simple, and the reagents used are all green and inexpensive common reagents. Moreover, the utilization rate of manganese raw materials is extremely high, basically reaching 100%.
Smart Images

Figure CN118162193B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of carbon capture catalyst preparation technology, and relates to a method for preparing a zeolite-supported MnOOH composite catalyst and its application. Background Technology
[0002] Carbon capture technologies, exemplified by organic amine absorption, serve as post-treatment technologies directly applied to industrial carbon emission reduction. However, the high energy consumption of organic amine regeneration severely limits the large-scale application of this process. Researchers have conducted extensive studies on how to reduce the desorption energy consumption of CO2-rich organic amines. Adding acidic catalysts during desorption to provide or transfer protons, thereby lowering the desorption temperature and increasing the desorption rate, achieves a dual effect of reducing energy loss and ammonia solution loss, making it one of the most promising technologies for reducing desorption energy consumption. Currently, the most commonly used desorption catalysts include metal oxides, solid superacids, and metal-organic framework materials.
[0003] Zeolites possess strong acidity and a large specific surface area, making them excellent catalytic materials widely used in catalytic desorption. However, a growing number of researchers have discovered that the acidity of zeolites is unstable in alkaline environments, and their bronsted acidic sites, after deprotonation, readily bind to amines, preventing further proton transfer for catalysis.
[0004] Currently, research on improving the stability of zeolite catalysis in the field of CO2-rich organic amine regeneration is limited, and there is a lack of effective methods to maintain both high catalytic efficiency and long-term stable reaction. Therefore, there is an urgent need to develop a new type of catalyst to address these issues and enhance the practical application potential of catalytic organic amine regeneration. Summary of the Invention
[0005] To address the aforementioned technical problems, one objective of this invention is to provide a method for preparing a zeolite-supported MnOOH composite catalyst in situ. Using zeolite as a carrier, MnOOH is grown in situ on the zeolite surface via a hydrothermal method. The loaded MnOOH is not easily detached and exhibits excellent stability. Another objective is to provide an application of the zeolite-supported MnOOH composite catalyst in the regeneration of CO2-rich organic amine solutions. The MnOOH-loaded zeolite exhibits weaker binding with alkaline substances, enabling stable catalytic regeneration. Furthermore, the composite catalyst requires a small amount of catalyst and consumes less energy.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing a zeolite-supported MnOOH composite catalyst in situ, comprising the following steps:
[0008] Zeolite, manganese source and reducing alcohol solvent were added to an aqueous solution in sequence, and then the solution was transferred to a reaction vessel for hydrothermal reaction. After the reaction was completed, the solution was centrifuged, washed and dried to obtain a composite catalyst.
[0009] Preferably, the zeolite is selected from HZSM-5, Mordenite, MCM-41, TNU-9, SSZ-35 or SBA-15.
[0010] Preferably, the manganese source is selected from one or more of potassium permanganate, manganese sulfate, manganese chloride, and manganese nitrate.
[0011] Preferably, the reducing alcohol solvent is selected from ethanol, ethylene glycol, n-propanol, or isopropanol.
[0012] Preferably, the amount of manganese source added is 10-50% of the mass of zeolite.
[0013] Preferably, the hydrothermal reaction conditions are as follows: stirring rate of 300-1500 r / min, reaction temperature of 60-180℃, and reaction time of 8-36 h.
[0014] Preferably, the drying conditions are as follows: drying temperature is 50-80℃, and drying time is 6-24h.
[0015] Secondly, the present invention provides the application of the composite catalyst prepared by the above preparation method in the regeneration of CO2-rich organic amine solution.
[0016] Preferably, the regeneration of CO2-rich organic amine solution includes the following steps: adding the composite catalyst to the CO2-rich organic amine solution, purging with nitrogen, and then heating in an oil bath to carry out the catalytic regeneration reaction.
[0017] Preferably, the amount of composite catalyst added to each 1L organic amine solution is 2-20g, and the concentration of CO2 in the organic amine solution is not less than 5mol / L.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0019] 1. This invention uses only one hydrothermal method to grow MnOOH in situ on the surface of zeolite. The preparation process is simple, and the reagents used are all green and inexpensive common reagents. Moreover, the utilization rate of manganese raw materials is extremely high, basically reaching 100%.
[0020] 2. The method of the present invention is applicable to various zeolites supporting MnOOH, with a wide range of applications. Furthermore, the composite catalyst has a hydrogen bond-like connection mode, which makes it difficult for MnOOH to fall off after loading, and it has good stability.
[0021] 3. The composite catalytic material prepared by the method of this invention exhibits unique advantages in the catalytic regeneration of CO2-rich organic amines. MnOOH is a good material for proton transfer, while zeolite is a commonly used material for catalytic regeneration of CO2-rich organic amines. However, zeolite has the inherent disadvantage of readily binding with alkaline substances. The combination of these two materials cleverly solves this problem. By loading MnOOH to alter the surface state of the zeolite, the binding between the zeolite and alkaline substances is weakened, allowing for stable catalysis. This composite form of zeolite-loaded metal hydroxyl oxide provides a simple and efficient catalytic regeneration of CO2-rich organic amine solutions, requiring only a small amount and low energy consumption. This type of zeolite-loaded MnOOH catalytic material can be applied in fields requiring proton transfer, such as the catalytic regeneration of CO2-rich organic amines, acid catalysis, and the catalytic degradation of formaldehyde. Attached Figure Description
[0022] Figure 1 This is the XRD pattern of the HZSM-5 / MnOOH series composite catalyst in Example 1, where... Figure 1 -a is the overall diagram with diffraction angles of 5-80°; Figure 1 -b is a magnified view of a local area with a diffraction angle of 25-27°.
[0023] Figure 2 This is the TG curve of the single MnOOH and HZSM-5 / MnOOH composite catalyst (MH20) in Example 1.
[0024] Figure 3 This is a graph showing the N2 gas adsorption-desorption curve of the HZSM-5 / MnOOH series composite catalyst synthesized in this invention.
[0025] Figure 4 These are XPS images of the HZSM-5 / MnOOH composite catalyst (MH20) synthesized in Example 1, and of single HZSM-5 and MnOOH. 4-a is a detailed view of Mn 2p; 4-b is a detailed view of O1s; 4-c is a detailed view of Si 2p; and 4-d is a detailed view of Al 2p.
[0026] Figure 5 This is the NH3-TPD diagram of the HZSM-5 / MnOOH series composite catalyst in Example 1.
[0027] Figure 6 This is a diagram of the reaction apparatus used to evaluate the regeneration performance of the catalyst in a CO2-rich organic amine solution according to the present invention.
[0028] Figure 7 This is a graph showing the catalytic regeneration performance of CO2-rich organic amines according to the present invention, wherein... Figure 7 -a is a graph showing the change in CO2 desorption rate over time. Figure 7 -b is a graph showing the change in the total amount of desorbed CO2 over time. Figure 7-c represents the relative energy consumption graph. Figure 7 -d is a graph showing the change in the total amount of CO2 desorbed after 6 cycles.
[0029] Figure 8 These are characterization diagrams of the HZSM-5 / MnOOH composite catalyst (MH20) synthesized in this invention before and after catalyzing the regeneration of CO2-rich organic amines. Figure 8 -a is the XRD pattern. Figure 8 -b represents the FT-IR plot. Figure 8 -c represents the SEM image. Detailed Implementation
[0030] The following embodiments are used to illustrate the present invention, but are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the test methods in the following embodiments are conventional methods.
[0031] Example 1: Synthesis of HZSM-5 / MnOOH Composite Catalyst
[0032] 0.5 g of HZSM-5 was dispersed in 60 ml of distilled water and stirred at 800 rpm for 3 min. Then, 0.05–0.15 g of KMnO4 was added and stirring continued for 30 min. Next, 3 mL of anhydrous ethanol was added and stirred for 5 min. The entire solution was then transferred to a 100 ml polytetrafluoroethylene (PTFE) reactor and reacted at 140 °C for 24 h. The reactor was then removed and cooled to room temperature. A brown precipitate was obtained and washed repeatedly by centrifugation with deionized water and anhydrous ethanol. The precipitate was then dried in an oven at 60 °C for 6 h to obtain the HZSM-5 / MnOOH composite catalyst series. Based on the amount of KMnO4 added (0.05 g, 0.1 g, and 0.15 g), they were named MH10, MH20, and MH30, respectively.
[0033] To verify the feasibility of the method and the structural characteristics and physicochemical properties of the obtained material, the synthesized material was partially characterized. Figure 1 This is the XRD pattern of the HZSM-5 / MnOOH series composite catalyst in Example 1, where... Figure 1 -a is the overall diagram with diffraction angles of 5-80°; Figure 1 -b is a magnified view of the diffraction angles from 25° to 27°. It can be seen that the XRD diffraction peaks of the obtained composite catalyst correspond one-to-one with the standard card.
[0034] Figure 2The image shows the TG curves of the single MnOOH and HZSM-5 / MnOOH composite catalyst (MH20) in Example 1. By comparing the weight loss of the single MnOOH and HZSM-5 / MnOOH composite catalyst, it can be determined that the Mn source is completely converted into MnOOH, proving that the method of the present invention is not only simple, but also has a high raw material utilization rate.
[0035] Figure 3 The graph shows the N2 gas adsorption-desorption curves of the HZSM-5 / MnOOH series composite catalysts in Example 1. It can be seen that the specific surface area and pore size distribution of MH10, MH20 and MH30 are among those of the single materials.
[0036] Figure 4 These are XPS images of the HZSM-5 / MnOOH composite catalyst MH20 synthesized in this invention, compared with those of single HZSM-5 and MnOOH. Figure 4 -a is a detailed image of Mn 2p. Figure 4 -b is a detailed view of O1s. Figure 4 -c is a detailed view of Si 2p. Figure 4 -d is a detailed image of Al2p. It can be seen that the chemical interaction between HZSM-5 and MnOOH is determined by the shift of the binding energy of Mn to lower values and the shift of the binding energies of Si and Al to higher values.
[0037] Figure 5 This is the NH3-TPD diagram of the HZSM-5 / MnOOH series composite catalysts synthesized in this invention. It can be seen that the adsorption of NH3 by the HZSM-5 / MnOOH composite catalyst gradually weakens, indirectly proving that loading MnOOH can effectively reduce the adsorption of amines.
[0038] Example 2 Synthesis of Mordenite / MnOOH composite catalyst
[0039] 0.5 g of Mordenite was dispersed in 60 ml of distilled water and stirred rapidly at 1200 rpm for 3 min. Then, 0.15 g of KMnO4 was added and stirring continued for 30 min. Next, 3 mL of anhydrous ethanol was added and stirring for 5 min. The entire solution was then transferred to a 100 ml polytetrafluoroethylene (PTFE) reactor and reacted at 140 °C for 24 h. The reactor was then removed and cooled to room temperature. A dark brown precipitate was obtained and washed repeatedly by centrifugation with deionized water and anhydrous ethanol. Finally, the precipitate was dried in an oven at 60 °C for 6 h to obtain the Mordenite / MnOOH composite catalyst.
[0040] Example 3: Synthesis of MCM-41 / MnOOH composite catalyst:
[0041] 0.5 g of MCM-41 was dispersed in 60 ml of distilled water and stirred at 500 rpm for 3 min. Then, 0.2 g of KMnO4 was added and stirring continued for 30 min. Next, 3 mL of anhydrous ethanol was added and stirred for 3 min. The solution was then transferred to a 100 ml polytetrafluoroethylene (PTFE) reactor and reacted at 140 °C for 18 h. The reactor was then removed and cooled to room temperature. A dark brown precipitate was obtained and washed repeatedly by centrifugation with deionized water and anhydrous ethanol. Finally, the precipitate was dried in an oven at 60 °C for 6 h to obtain the MCM-41 / MnOOH composite catalyst.
[0042] Example 4: Synthesis of HZSM-5 / MnOOH Composite Catalyst
[0043] 0.4 g of HZSM-5 was dispersed in 60 ml of distilled water and stirred rapidly at 1500 rpm for 3 min. Then, 0.1 g of KMnO4 was added and stirring continued for 30 min. Next, 3 mL of isopropanol and 0.1 g of MnSO4 were added and stirred for 3 min to dissolve. The solution was then transferred to a 100 ml polytetrafluoroethylene (PTFE) reactor and reacted at 140 °C for 8 h. The reactor was then removed and cooled to room temperature. A dark brown precipitate was obtained and washed repeatedly by centrifugation with deionized water and anhydrous ethanol. Finally, the precipitate was dried in an oven at 60 °C for 6 h to obtain the HZSM-5 / MnOOH composite catalyst.
[0044] Example 5 Synthesis of Mordenite / MnOOH Composite Catalyst
[0045] 0.5 g of Mordenite was dispersed in 60 ml of distilled water and stirred at 300 rpm for 3 min. Then, 0.1 g of KMnO4 was added and stirring continued for 30 min. Next, 3 mL of isopropanol and 0.1 g of MnSO4 were added and stirred for 3 min to dissolve. The solution was then transferred to a 100 ml polytetrafluoroethylene (PTFE) reactor and reacted at 140 °C for 30 h. The reactor was then removed and cooled to room temperature. A dark brown precipitate was obtained and washed repeatedly by centrifugation with deionized water and anhydrous ethanol. Finally, the precipitate was dried in an oven at 60 °C for 6 h to obtain the Mordenite / MnOOH composite catalyst.
[0046] Example 6 Synthesis of MCM-41 / MnOOH composite catalyst
[0047] 0.8 g of MCM-41 was dispersed in 60 ml of distilled water and stirred at 1200 rpm for 3 min. Then, 0.2 g of KMnO4 was added and stirring continued for 30 min. Next, 5 mL of anhydrous ethanol and 0.1 g of MnCl3 were added and stirred for 3 min to dissolve. The solution was then transferred to a 100 ml polytetrafluoroethylene (PTFE) reactor and reacted at 140 °C for 12 h. The reactor was then removed and cooled to room temperature. A dark brown precipitate was obtained and washed repeatedly by centrifugation with deionized water and anhydrous ethanol. Finally, the precipitate was dried in an oven at 60 °C for 8 h to obtain the MCM-41 / MnOOH composite catalyst.
[0048] Experimental Example 1
[0049] In such Figure 6 The catalytic regeneration reaction was carried out in the reaction system shown. 0.1 g of the HZSM-5 / MnOOH series composite catalysts (MH10, MH20, MH30), HZSM-5, and MnOOH prepared in Example 1 were dispersed in 50 mL of a 5 mol / L CO2-rich monoethanolamine solution. The entire process was carried out under a high-purity nitrogen gas flow rate of 600 mL / min. The system was first purged of air for 5 min. Then, the oil bath heating switch was turned on, and the temperature was set from 30 to 90 °C to carry out the catalytic regeneration reaction. A CO2 infrared detector recorded the changes in CO2 concentration in the gas flow in real time, and the CO2 desorption rate was calculated.
[0050] Figure 7 This is a graph showing the catalytic regeneration performance of CO2-rich organic amines according to the present invention, wherein... Figure 7 -a is a graph showing the change in CO2 desorption rate over time. Figure 7 -b is a graph showing the change in the total amount of desorbed CO2 over time. Figure 7 -c represents the relative energy consumption graph. Figure 7 -d is a graph showing the change in total CO2 desorption after 6 cycles. The results show that after 100 min of desorption, the amount of CO2 desorbed by the HZSM-5 / MnOOH series composite catalyst is greater than that without catalyst and with single material, with the highest being 1.7 times that without catalyst; the relative energy consumption is also reduced by 26-32%; it not only has high catalytic capacity, but also excellent recycling performance, with the catalytic capacity decreasing by less than 10% after 6 cycles.
[0051] Figure 8 These are characterization diagrams of the HZSM-5 / MnOOH composite catalyst (MH20) synthesized in this invention before and after catalyzing the regeneration of CO2-rich organic amines. Figure 8 -a is the XRD pattern. Figure 8 -b represents the FT-IR plot. Figure 8 -c is the SEM image. It can be seen that the crystal structure and surface state of the catalyst remained basically unchanged after cycling.
[0052] Experimental Example 2
[0053] Take 0.1g of the Mordenite / MnOOH composite catalyst prepared in Example 2 and disperse it in 50ml of a 5mol / L CO2-rich monoethanolamine:polyethylenepolyamine mixed solution (1:1). Figure 6 The catalytic regeneration reaction was carried out in the reaction system shown. The entire process was conducted under a high-purity nitrogen gas flow of 600 mL / min. Air was first purged from the system for 5 minutes. Then, the oil bath heating switch was turned on, and the temperature was set from 30 to 90 °C for the catalytic regeneration reaction. A CO2 infrared detector recorded the changes in CO2 concentration in the gas flow in real time, and the CO2 desorption rate was calculated. The results showed that after 100 minutes of desorption using the Mordenite / MnOOH composite catalyst, the amount of CO2 desorbed increased by 23% compared to the catalyst-free system; the relative energy consumption also decreased by 21%.
[0054] The embodiments described above are merely preferred embodiments of the present invention and are only used to explain the present invention. They are not intended to limit the scope of the present invention. For those skilled in the art, other implementation methods can be easily made by substitution or modification based on the technical content disclosed in this specification. Therefore, all changes and improvements made on the principle of the present invention should be included within the scope of the patent application of the present invention.
Claims
1. The application of a zeolite-supported MnOOH composite catalyst in the regeneration of CO2-rich organic amine solutions, characterized in that, The preparation method of zeolite-supported MnOOH composite catalyst includes the following steps: zeolite, manganese source and reducing alcohol solvent are added to an aqueous solution in sequence, and then the solution is transferred to a reaction vessel for hydrothermal reaction. After the reaction is completed, the solution is centrifuged, washed and dried to obtain the composite catalyst.
2. The application according to claim 1, characterized in that, The process includes the following steps: adding the composite catalyst to a CO2-rich organic amine solution, purging with nitrogen, and then heating in an oil bath to carry out the catalytic regeneration reaction.
3. The application according to claim 1, characterized in that, The amount of composite catalyst added per 1L of organic amine solution is 2~20 g.
4. The application according to claim 1, characterized in that, The zeolite is selected from HZSM-5, mordenite, MCM-41, TNU-9, SSZ-35 or SBA-15.
5. The application according to claim 1, characterized in that, The manganese source is selected from one or more of potassium permanganate, manganese sulfate, manganese chloride, and manganese nitrate.
6. The application according to claim 1, characterized in that, The reducing alcohol solvent is selected from ethanol, ethylene glycol, n-propanol, or isopropanol.
7. The application according to claim 1, characterized in that, The amount of manganese source added is 10-50% of the mass of zeolite.
8. The application according to claim 1, characterized in that, The hydrothermal reaction conditions are as follows: stirring rate of 300~1500 r / min, reaction temperature of 60~180 ℃, and reaction time of 8~36 h.
9. The application according to claim 1, characterized in that, The drying conditions are as follows: drying temperature is 50~80 ℃, and drying time is 6~24 h.